1980
DOI: 10.1192/bjp.136.5.498
|View full text |Cite
|
Sign up to set email alerts
|

Tryptophan, Cortisol and Puerperal Mood

Abstract: Plasma cortisol, free and total tryptophan were determined in 71 subjects on 8 occasions between 36 weeks gestation and 6 weeks post-partum. Affect was measured by rating scales and clinical interview. Twenty-eight subjects were judged to have experienced post-partum 'blues'. Seasonal variation occurred in the incidence of 'blues' and in cortisol and free tryptophan levels. Puerperally-depressed mood was correlated with high cortisol at 38 weeks irrespective of season. Free tryptophan was reduced in 'blues' su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
107
1
3

Year Published

1981
1981
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(115 citation statements)
references
References 34 publications
3
107
1
3
Order By: Relevance
“…Women experiencing postpartum blues seem to be somewhat more likely to have poor family or marital relations and to have experienced mood disturbances before or during pregnancy (Ballinger, Kay, Naylor, & Smith, 1982;Cutrona, 1983;Handley, Dunn, Waldron, & Baker, 1980;Kennerley & Gath, 1989b;Nott, Franklin, Armitage, & Gelder, 1976). Currently, no available evidence links postpartum blues to adverse effects on children and the condition on its own will not be discussed further.…”
Section: Postpartum Depression: Implications For Infants' Emerging Comentioning
confidence: 87%
“…Women experiencing postpartum blues seem to be somewhat more likely to have poor family or marital relations and to have experienced mood disturbances before or during pregnancy (Ballinger, Kay, Naylor, & Smith, 1982;Cutrona, 1983;Handley, Dunn, Waldron, & Baker, 1980;Kennerley & Gath, 1989b;Nott, Franklin, Armitage, & Gelder, 1976). Currently, no available evidence links postpartum blues to adverse effects on children and the condition on its own will not be discussed further.…”
Section: Postpartum Depression: Implications For Infants' Emerging Comentioning
confidence: 87%
“…For example, even though plasma tryptophan concentration decreases progressively during pregnancy and ordinarily recovers normal values after delivery, a reduction of plasma tryptophan levels during the post-partum period has been suggested to contribute to the onset of symptoms of postpartum depression in some women (Handley et al, 1980;Maes et al, 2002;Schrocksnadel et al, 2003). Supporting this hypothesis, normal healthy women experienced a marked decrease in several parameters of mood following tryptophan depletion, whereas men did not (Ellenbogen et al, 1996).…”
Section: -Ht Microdialysis Measurementmentioning
confidence: 99%
“…Postpartum depression must be distinguished from the "baby blues," which occur in the majority of new mothers. This transient mood disturbance does not consistently affect the woman's ability to function [9]. According to Stein's criteria, 67% of postpartum women have been diagnosed as suffering from MB [10], while studies focused on the Japanese population reported that only 15-35% women were affected [11][12][13].…”
Section: Introductionmentioning
confidence: 99%